Rapid photoprotection in sea-ice diatoms from the East Antarctic pack ice - Petrou, K; Hill, R; Brown, CM; Campbell, DA; Doblin, MA; Ralph, PJ (2010)
Photoinhibition and D1 protein re-synthesis were investigated in bottom-dwelling sea-ice microalgal communities from the East Antarctic pack ice during early spring. Bottom-dwelling sea-ice microalgal communities were dominated by diatoms that exhibited rapid photoprotection when exposed to a range of different light levels (10 μmol photons m-2 s -1, 50 μmol photons m-2 s-1, 100 μmol photons m-2 s-1, and 200 μmol photons m-2 s-1). Photosynthetic capacity of photosystem II (PSII) dropped significantly over 3 h under 200 μmol photons m-2 s-1, but largely recovered when placed in a low-light environment (10 μmol photons m-2 s-1) for an additional 3 h. PSII repair rates increased with increasing irradiance, and the D1-protein pool remained steady even under high light (200 μmol photons m-2 s-1). Sea-ice diatoms showed a low intrinsic susceptibility to photoinactivation of PSII across all the light treatments, and a strong and irradiance-dependent induction of nonphotochemical quenching, which did not depend upon chloroplast protein synthesis, was also seen. These highly plastic organisms, once thought to be adapted to shade, are in fact well equipped to withstand rapid and relatively large changes in light at low temperatures with minimal long-term effect on their photosynthetic machinery. © 2010, by the American Society of Limnology and Oceanography, Inc.